The Health Education Demonstration Methods to Increase the Knowledge Level of Prevention of the Corpus Alienum of Eye toward Welding Workers - Siswoyo Siswoyo; Kushariyadi Kushariyadi; Nur Winingsih (Faculty of Nursing, Universitas Jember, 2018)
Corpus alienum is any object or substance found in an organ or tissue in which it does not belong under normal circumstances. Corpus alienum of eye can be experienced by welder that do not use eye protective equipment. Health education with demonstration methods is one of the learning methods to improve the knowledge. The purpose of this research is to know the influence of health education by demonstration method toward the knowledge level of the corpus alienum eye’s prevention in welder. This research used pre-experimental with one group pretest-posttest design. The sampling technique was non-probability samplig used total sampling involving 16 respondents. The data were statistically analyzed using wilcoxon test. The result of data analyze showed a significant value (p value = 0.005). Health education with demonstration methods can improve the knowledge of welder so can be minimized the risk of corpus alienum of eye. There were correlation between health education of demonstration methods and the knowledge level of prevention of the corpus alienum of eye to welder in Putra Jaya Sumbersari the districts of Jember. It is expected that nurses can do health education demonstration methods to prevent corpus alienum of eye in welder to be minimized the risk of corpus alienum of eye.